Determination of n-alkanes contamination in soil samples by micro gas chromatography functionalized by multi-walled carbon nanotubes. (September 2016) - Li, Yubo; Zhang, Runzhou; Wang, Tao; Wang, Yonghuan; Xu, Tianbai; Li, Lingfeng; Zhao, Weijun; Dong, Shurong; Wang, Xiaozhi; Luo, Jikui
Abstract: A new method for separation of 11 n -alkanes: octane, o -nonane, n -decane, n -undecane, n -dodecane, n -tridecane, n -tetradecane, n -pentdecne, n -hexadecath, heptadecane, n -octadecane in soil samples was developed. Kuderna-Danish (K.D.) concentrator enrichment prior to ultrasonic extraction and the silicone chromatography column purification and with gas chromatography flame ionization detection (GC-FID) could be used for n -alkanes determination. The micro channels of open tubular column were fabricated onto a silicon wafer to replace the quartz capillary chromatographic column. The column structure and analysis parameters that affected the column separation were investigated and optimized. Under optimal conditions, the extract reagent was centrifuged and collected. A silicone chromatography column and a K.D. concentrator were used for further clean-up and enrichment. Using this method, the limits of detection (LOD) and limits of quantification (LOQ) were obtained in the range of 0.03–0.15 and 0.1–0.5 mg kg −1 in soil samples, respectively. The relative standard deviation (RSD) was under 12%. The optimized procedure that presented good analytical performance (with recoveries ranging from 56.5% to 89.2%), was successfully applied to determine n -alkane content in farmland soil samples adjacent to a highway. The results showed that the MWCNTs-functionalized column is capable of separating the alkane contaminations with high resolution in about 3 min, which is much shorter than that of GC-MS and other conventional analytical methods, demonstrating its great potential for rapid analysis. Graphical abstract: Highlights: The micro channels of open tubular column were fabricated onto a silicon wafer. The micro column stationary phase was functionalized by multi-walled carbon nanotubes. The micro column was successfully separated eleven n -alkanes in soil samples. The separation time was very short (3.5 min) when compared with the GC/MS (35 min). This new method provides a huge potential application value for rapid analytical fields.